Praxis of Teachers' Power Relations on Students Discipline in Elementary School - Tamara; Yepi Ramada R; Saras; Ronaldo; Yulianus Celcius Abidondifu (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to find a relationship between teacher power and the discipline of students in elementary schools in Palangka Raya City. This research method uses qualitative research with interview techniques. Data was collected by giving questions to 3 informants, namely educators. The results of the author's research show that rules or regulations at school are able to provide knowledge about discipline to students and invite them to comply with the regulations that have been implemented. The results of the study show that dress discipline, discipline, crafts and teacher support are in the good category.